Stimulating embodied intersubjectivities: two participatory experiments in Antwerp North, Belgium. Issue 3 (3rd July 2022) - Devos, Tim; Loopmans, Maarten
ABSTRACT: This paper argues how communicative planning approaches, as one of the most dominant conceptualisations of participatory planning, often ignore the embodied dimensions of participation as a socio-political learning processes. To do so, the paper theoretically traces why a Habermasian conceptualisation of political intersubjectivity fails to democratise planning processes and turns to an alternative Mouffean framework where coproductive methods are conceptualised as public pedagogic interventions, allowing for different meanings to be created and shared in a dialogical process. Based on an analysis of two experiments the authors have conducted, some lessons are drawn on how specific methods can be designed to stimulate more embodied forms of intersubjectivity between involved actors, while avoiding top-down consensus-making. In this way, the analysis demonstrates how such methods stimulate participants to share experiences, while orienting the discussion in a spatialised direction and creating a space where the ambivalence of place is effectively stimulated.